Implementasi Program Keputrian dalam Meningkatkan Pemahaman Fiqih Wanita di SMP Uluwwul Himmah - Atika Khairunnisa; Mavianti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Women's activities are a forum for female students to gain insight into women's problems. This research aims to describe the implementation of the women's program at Uluwwul Himmah Middle School to increase women's understanding of jurisprudence. This research uses a qualitative approach. The data collection methods used were observation, interviews and documentation. The results of the research obtained are (1) Planning to support successful learning, which includes: a. Determining goals, b. Determining teaching materials/materials, c. Determine the method, d. Determine time allocation. (2) Implementation of the princess program is the implementation of planning for the girls program, which includes the opening and formation of student competencies. (3) Evaluation of the girls program by observing changes in students' attitudes before and after taking part in the girls program. (4) The results of the women's program include improving students' character education, increasing students' skills and knowledge, and increasing students' insight into women's jurisprudence material. (5) Supporting and inhibiting factors, supporting factors: The school provides adequate facilities and complete support. Inhibiting factors: female students are less enthusiastic about participating in women's activities. The girlhood program carried out at Uluwwul Himmah Middle School must continue to be implemented and developed so that it can produce equitable education and more benefits.